2022
DOI: 10.3389/fnut.2022.979609
|View full text |Cite
|
Sign up to set email alerts
|

Steam explosion processing intensifies the nutritional values of most crop byproducts: Morphological structure, carbohydrate-protein fractions, and rumen fermentation profile

Abstract: To investigate the feasibility of steam explosion on the exploitation of ruminant feedstuff, the morphological structure, carbohydrate-protein fractions, and rumen fermentation profile of five typical crop byproducts (corn cob, rice straw, peanut shell, millet stalk, and sugarcane tip) were analyzed before and after steam explosion processing. The results showed that these crop byproducts had different physicochemical properties and rumen fermentation profiles, most of which could be improved by steam explosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The present study shows that the complete substitution of CSC with WBTS results in 10-20% increased concentrations of ruminal C3 proportion, whereas decreased proportions of C2 are due to the fact that in the rumen, the metabolic pathways for C3 creation are more effective at transforming energy than those for C2 and C4 production [3,10]. He et al [22] suggested that ruminants may benefit from a more effective source of energy supply if they were fed steam feedstuffs. It's probable that the steam-flaking process broke down the protein's disulfide bond and the starch's embedded structure, making the starch surface more palatable for ruminal microbial breakdown enzymes [20,21], hence enhancing the starch's ruminal degradability when fed at a replacement optimal level of 10 to 25% of concentrate, which improved the degradability of starch and ruminal fermentation in the rumen [7,21].…”
Section: Volatile Fatty Acid Profilesmentioning
confidence: 58%
See 3 more Smart Citations
“…The present study shows that the complete substitution of CSC with WBTS results in 10-20% increased concentrations of ruminal C3 proportion, whereas decreased proportions of C2 are due to the fact that in the rumen, the metabolic pathways for C3 creation are more effective at transforming energy than those for C2 and C4 production [3,10]. He et al [22] suggested that ruminants may benefit from a more effective source of energy supply if they were fed steam feedstuffs. It's probable that the steam-flaking process broke down the protein's disulfide bond and the starch's embedded structure, making the starch surface more palatable for ruminal microbial breakdown enzymes [20,21], hence enhancing the starch's ruminal degradability when fed at a replacement optimal level of 10 to 25% of concentrate, which improved the degradability of starch and ruminal fermentation in the rumen [7,21].…”
Section: Volatile Fatty Acid Profilesmentioning
confidence: 58%
“…According to Makizadeh et al [34], slow-fermented starch treated with steam produced high short-chain fatty acids (SCFA). Similarly, He et al [22] suggested that raw material and steam processing in millet stalks and sugarcane tips could decrease the C2:C3 molar ratio and increase the molar proportion of C3. However, flaking and steaming changed the amylopectin in grains or cereals by turning it…”
Section: Volatile Fatty Acid Profilesmentioning
confidence: 97%
See 2 more Smart Citations
“…The structure of SDF from Tartary buckwheat bran with SE treatment (1.2 Mpa, 90 s) was changed noticeably. The physical and chemical properties and hypoglycemic function in vivo of SDF were also significantly improved (He, Huang, et al, 2022). Animal experiments have shown that SE can reduce blood glucose levels in diabetic mice, regulate the intestinal microbiota and insulin resistance in diabetic mice, and protect the liver and pancreas of mice.…”
Section: Physicochemical and Functional Properties Of Dietary Fibermentioning
confidence: 99%